If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4 = -2x + 12 Reorder the terms: -4 + 2x = -2x + 12 Reorder the terms: -4 + 2x = 12 + -2x Solving -4 + 2x = 12 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -4 + 2x + 2x = 12 + -2x + 2x Combine like terms: 2x + 2x = 4x -4 + 4x = 12 + -2x + 2x Combine like terms: -2x + 2x = 0 -4 + 4x = 12 + 0 -4 + 4x = 12 Add '4' to each side of the equation. -4 + 4 + 4x = 12 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = 12 + 4 4x = 12 + 4 Combine like terms: 12 + 4 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| Y=6x-37 | | a/-7-2=10 | | X+2/2=x/8 | | q=p+prt | | 2(5x-6)=6 | | 5/x=30/2 | | Y=7x+36 | | (1/6)(5x+7)=7x | | 3x^3-2x^2+18x+56=0 | | 1/4y^2-1=0 | | X/12=4/24 | | (x-1)=-4x+34 | | -a/10=-24 | | 1/2x^2+4x=0 | | 3+6=58+x | | 6x-y=-28 | | x/7+x/8+15/56 | | 4/p=12/5 | | 2y+(1/3)=(7/3) | | x/0.3=0.012 | | 0.3x=0.012 | | 7x-15=-120 | | x+0.3=0.2 | | x+0.2=0.3 | | x+10=-7 | | 1/3*t^2-9=0 | | 17+3=27+x | | X^2+20x+12=0 | | -16x^2+26x+100=0 | | -2x-5=3x-5 | | 2/5*10/9 | | 81x*x=24x |